Emergent multiferroism with magnetodielectric coupling in EuTiO3 created by a negative pressure control of strong spin-phonon coupling - Run Zhao (Nature Communications, 2022)
Negative pressure tailors the physical properties of functional oxide materials. Here, the authors demonstrate an emergent multiferroism with magnetodielectric coupling in EuTiO3 created by a negative pressure control of strong spin-phonon coupling.